2004
DOI: 10.1093/nar/gkh863
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal  O helix of human Ogg1 is essential for 8-oxoguanine DNA glycosylase activity: the mitochondrial  -Ogg1 lacks this domain and does not have glycosylase activity

Abstract: The human Ogg1 glycosylase is responsible for repairing 8-oxo-7,8-dihydroguanine (8-oxoG) in both nuclear and mitochondrial DNA. Two distinct Ogg1 isoforms are present; alpha-Ogg1, which mainly localizes to the nucleus and beta-Ogg1, which localizes only to mitochondria. We recently showed that mitochondria from rho(0) cells, which lack mitochondrial DNA, have similar 8-oxoG DNA glycosylase activity to that of wild-type cells. Here, we show that beta-Ogg1 protein levels are approximately 80% reduced in rho(0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 44 publications
0
81
1
Order By: Relevance
“…Compared with nuclear DNA, the mutation and damage rate of mtDNA by oxidative stress is severalfold higher in part because of the close proximity of mtDNA to the electron transport chain-generating ROS, the lack of histone-containing proteins that shield mtDNA, and the limited mtDNA repair systems (1)(2)(3)(4)(5)(6). A novel finding of this study is that mt-hOgg1-Mut, which lacks the crucial amino acids necessary for 8-oxoG DNA repair (25), prevents oxidant-induced AEC mtDNA damage in a manner similar to mt-hOgg1-WT (Fig. 2).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Compared with nuclear DNA, the mutation and damage rate of mtDNA by oxidative stress is severalfold higher in part because of the close proximity of mtDNA to the electron transport chain-generating ROS, the lack of histone-containing proteins that shield mtDNA, and the limited mtDNA repair systems (1)(2)(3)(4)(5)(6). A novel finding of this study is that mt-hOgg1-Mut, which lacks the crucial amino acids necessary for 8-oxoG DNA repair (25), prevents oxidant-induced AEC mtDNA damage in a manner similar to mt-hOgg1-WT (Fig. 2).…”
Section: Discussionmentioning
confidence: 70%
“…2). Notably, mt-Ogg1-Mut, which is incapable of DNA repair yet able to block intrinsic AEC apoptosis (11,25), also prevented oxidantinduced AEC mtDNA damage and intrinsic apoptosis similar to mt-hOgg1-WT (Fig. 2).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Purification of full-length, His 6 -tagged human RAD52 has been described previously (2). Purification of recombinant Histagged OGG1-␣ from Sf9 insect cells and His-and glutathione S-transferasetagged OGG1-␤ from E. coli has been described (13). Oligonucleotides were obtained from Midland Certified Reagent Co., and their sequences are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…While OGG1-␣ is a bone fide DNA glycosylase (5) and localizes both to nuclei and mitochondria, OGG1-␤ localizes exclusively to mitochondria. We recently showed that the recombinant OGG1-␤ protein has no DNA glycosylase activity (13). The high degree of conservation of repair pathways for 8-oxoG, from bacteria to humans, along with epidemiological data correlating OGG1 polymorphisms and activity with predisposition to some cancers (11,27,33) attest to the biological importance of the repair of 8-oxoGs and other oxidative DNA lesions.…”
mentioning
confidence: 99%